Pelaksanaan Literasi pada Kegiatan Membuka Pembelajaran di kelas 5A SDN 71 Kota Bengkulu - Anis, Anis Fahmi Andini; Susanti, Atika (Universitas Bengkulu, 2024)
This research aims to describe the implementation of literacy in opening learning activities in class 5A of SDN 71 Bengkulu City. The research used is qualitative and descriptive methods. The research subjects were teachers and students class 5 A. The instrument this research was the invertigator himself, while the supporting instruments were observation sheets, interview sheets and documentation. Data collecting technique use observation, interviews and documentation. Data analysis is used by collecting data, reduction data, presenting data and draw a conclusion. Testing the validity of the data using triangulation,member check and extension of observation. The results of the research are (1) literacy using story books and various reading texts (2) strategy when reading by reading silently and reading together with one student reading and the other students listening, (3) teacher and students when reading , (4) follow-up after reading, namely in the form of question and answer activities between the teacher and students regarding the reading, making a summary, and presenting the summary results and (5) suggestions and input from the teacher. It can be concluded that literacy implementation activities in opening learning activities in class 5A SDN 71 Bengkulu city have been carried out well, where teachers and students are used to carrying out literacy activities in initial learning activities.